Kliinilise järelauditi „Insuldiravi põhjendatus ja kvaliteet Eesti haiglates“ kokkuvõte - Kõrv, Janika; Heinsoo, Maris; Kreis, Andrus; Kullamaa, Silja; Liigant, Aive; Õunapuu, Anne (Eesti Arst, 2016)
Eesti Arst 2016; 95(1):17–19